2020
DOI: 10.1002/brb3.1522
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between prenatal exposure to maternal obesity and hippocampal volume in children

Abstract: Introduction Animal studies have shown that male but not female offspring exposed to maternal obesity have abnormal hippocampal development. Similar sex differences were observed in animal models of developmental programming by prenatal stress or maternal diabetes. We aimed to translate this work into humans by examining sex‐specific effects of exposure to maternal obesity on hippocampal volume in children. Methods Eighty‐eight children (37 boys and 51 girls) aged 7–11 years completed the study. Maternal prepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…shown that the hippocampus of boys is particularly sensitive to in utero metabolic insults (Alves et al, 2020;Zhu et al, 2018). Importantly, while the interaction with GDM exposure and sex on child hippocampal volume and right CA1 subfield volume was independent of age and intracranial volume, sex stratified results in boys were no longer significant after adjusting for age and intracranial volume.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…shown that the hippocampus of boys is particularly sensitive to in utero metabolic insults (Alves et al, 2020;Zhu et al, 2018). Importantly, while the interaction with GDM exposure and sex on child hippocampal volume and right CA1 subfield volume was independent of age and intracranial volume, sex stratified results in boys were no longer significant after adjusting for age and intracranial volume.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the hippocampus exhibits a high metabolic demand (Jabès, Lavenex, Amaral, & Lavenex, 2011;Kirschen, Kéry, & Ge, 2018), which makes it susceptible to perturbations in vital nutrients, such as glucose, iron and oxygen. Moreover, prior neuroimaging studies have shown that prenatal exposure to alcohol or maternal obesity preferentially impacts hippocampal volume of offspring, most notably in a sex-specific manner (Alves et al, 2020;Treit et al, 2017). Collectively, prior studies provide evidence that the hippocampus may be particularly sensitive to in utero insults.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Studies in rodents and humans link maternal obesity to neurological changes in offspring. A recent human study reported a negative association between maternal BMI and hippocampal volume in male children at 7–11 years of age [ 76 ]. Furthermore, consumption of diets high in polyunsaturated omega-6 fatty acids during pregnancy impairs healthy brain structure and development in the foetus.…”
Section: Underlying Mechanisms By Which Maternal Obesity Programs mentioning
confidence: 99%